Density functional theory of nematic elasticity: softening from the polar order. Issue 23 (20th May 2016) - De Gregorio, Paolo; Frezza, Elisa; Greco, Cristina; Ferrarini, Alberta
Abstract : In nematic liquid crystals made of polar-shaped particles, the onset of polar order can greatly reduce the cost for splay and bend deformations. Abstract : Recent experiments have evidenced some unconventional features in the elasticity of nematics, which cannot be explained by standard microscopic theories. Here, in the framework of a second-virial density functional theory, we have developed a general approach, relaxing the usual assumption that the angular distribution of particles with respect to their local director is unaffected by the deformation. We show that, for particles with polar symmetry, a new contribution to the splay and bend deformation free energy arises, associated with the onset of polar order. Calculations for conical and bent-shaped particles reveal dramatic softening of the splay and the bend mode, respectively, which eventually may lead to spontaneous deformation.